2004
DOI: 10.1183/09031936.04.00034304
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality in COPD among construction workers exposed to inorganic dust

Abstract: The aim of this study was to find out if occupational exposure to dust, fumes or gases, especially among never-smokers, increased the mortality from chronic obstructive pulmonary disease (COPD).A cohort of 317,629 Swedish male construction workers was followed from 1971 to 1999. Exposure to inorganic dust (asbestos, man-made mineral fibres, dust from cement, concrete and quartz), gases and irritants (epoxy resins, isocyanates and organic solvents), fumes (asphalt fumes, diesel exhaust and metal fumes), and woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(132 citation statements)
references
References 35 publications
2
122
1
7
Order By: Relevance
“…In miners and construction workers, dust exposure tends to increase the incidence for chronic bronchitis Bergdahl et al 2004) as well as for asthma Karjalainen et al 2002a). An interesting question is why some individuals show higher risks of developing asthma and yet others develop chronic bronchitis after exposure to irritants.…”
Section: Synthesis With Previous Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…In miners and construction workers, dust exposure tends to increase the incidence for chronic bronchitis Bergdahl et al 2004) as well as for asthma Karjalainen et al 2002a). An interesting question is why some individuals show higher risks of developing asthma and yet others develop chronic bronchitis after exposure to irritants.…”
Section: Synthesis With Previous Knowledgementioning
confidence: 99%
“…Our first study was performed on cases diagnosed 1950 -1990 in two communities with dominating wood industry (Flodin et al 1996), the second study encompassed cases of asthma diagnosed 1960 -1997 in a metal industry dominated community ( Flodin et al 2004). Those two studies found an significant excess risk for asthma in subjects having worked for at least tree years in non sensitising air polluted workshops.…”
Section: Introductionmentioning
confidence: 99%
“…Además, los menores valores de flujo espiratorio pico se asociaban a la condición socioeconómica (45), a un mayor tiempo de residencia en el barrio y a la exposición ocupacional previa (46)(47)(48).…”
Section: Discussionunclassified
“…Industryand population-based epidemiological studies have reported increased risk of COPD due to occupational exposures or due to employment in certain industries or job categories. Occupational groups reported to have increased risk of COPD include coal miners, hard rock miners, tunnel workers, concretemanufacturing workers, construction workers, agricultural workers, and some manufacturing workers [2,3,[6][7][8][9]. COPD etiology is multi-factorial in nature and is strongly associated with non-occupational factors such as tobacco smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Although cigarette smoking is the most important risk factor worldwide for COPD, occupational exposures to mineral and organic dusts, irritant gases and fumes, and to other industrially produced or used agents have been established as risk factors for COPD [2][3][4][5][6][7][8][9][10][11][12][13][14]. Industryand population-based epidemiological studies have reported increased risk of COPD due to occupational exposures or due to employment in certain industries or job categories.…”
Section: Introductionmentioning
confidence: 99%